Peningkatan Keterampilan Budi Daya Ternak Ayam Kampung di Desa Karangsari, Pengasih, Kulon Progo - Arie Kusuma Paksi; Zuhud Rozaki (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic has negatively impacted the whole globe indiscriminately––including Indonesia, especially in the economy aspect. A significant increase in the unemployment rate forces people to strive harder in order to meet their needs. In Karangsari Village, Pengasih, Kulon Progo Regency, Yogyakarta Special Region (DIY), the Sendang Rejeki Women Farmers Group (KWT), for instance, initiated the establishment of free-range chicken farm, in order to deal with their dropping income and unemployment. Free-range chicken farming itself is a very significant business with a growing demand every year. On its process, the Sendang Rejeki Women Farmers Group (KWT) faces several challenges such as limited exposure in business development, inability to use the latest technology, lack of incubators and weak promotional strategies. Therefore, the community service team offer assistance in the form of knowledge transfer on technology and business development, which eventually could help the local community to boost the promotion of free-range chicken farm. The proposed strategy is expected to contribute in reducing unemployment rates and improving the income of the community in Karangsari Village.